2023
DOI: 10.1002/adhm.202203085
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: The Entanglement between Traditional Drugs and Nanodrugs in Tumor Therapy

Abstract: Ferroptosis is a non‐apoptotic programmed cell death caused by the accumulation of lipid peroxide. System Xc‐/glutathione peroxidase 4 (GPX4) axis and iron axis are two main pathways regulating ferroptosis. Simultaneously, multiple pathways are also involved in the ferroptosis regulation. Ferroptosis is an intense area of the current study. With the improvement of the regulatory mechanisms that underlie ferroptosis, a variety of drugs associated with ferroptosis have been discovered and developed for cancer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 191 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…Firstly, BPQDs, as a highly safe nanomedicine, overcome the limitations of traditional small molecule drugs, such as uncertain safety, short half-life, low bioavailability, poor targeting, and unstable e cacy 16,17 . Secondly, BPQDs possess a relatively loose molecular structure and abundant surface active sites 66,67 , allowing them to adsorb and undergo covalent bonding with other drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, BPQDs, as a highly safe nanomedicine, overcome the limitations of traditional small molecule drugs, such as uncertain safety, short half-life, low bioavailability, poor targeting, and unstable e cacy 16,17 . Secondly, BPQDs possess a relatively loose molecular structure and abundant surface active sites 66,67 , allowing them to adsorb and undergo covalent bonding with other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the safety of other available ferroptosis inhibitors within the eye still needs to be determined. These ferroptosis inhibitors are all small-molecule drugs with potential drawbacks such as a short half-life, low bioavailability, poor targeting, and unstable e cacy 16,17 . Thus, a more suitable and safer ferroptosis inhibitor (especially a nano-drug) is urgently required, which will signi cantly facilitate the treatment of glaucoma and other ferroptosis-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of ferroptosis nanoparticles has been promoted by research on nano-delivery systems. 116 Most ferroptosis inducers are small molecule drugs that have direct effects on disease targets. Small molecule drugs also have the cost advantages of low price and mature technology.…”
Section: The Application Of Nanoparticles Based On Ferroptosis In Can...mentioning
confidence: 99%
“…Ferroptosis was discovered long before the concept of ferroptosis was established in 2012. 1 Several studies have revealed that controlling or triggering ferroptosis can be advantageous in the treatment of various medical conditions, such as degenerative diseases, ischemic organ damage and cancer. 2,3 For cancer treatment, traditional treatments, including surgery, chemotherapy, and radiation therapy, are often not as effective as desired due to factors like drug resistance, treatment efficiency, and toxic side effects.…”
Section: Introductionmentioning
confidence: 99%